Rytualne aspekty kampanii wyborczych - Churska, Karolina (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Rituals reflect individual needs on the one hand and enable a social or political balance to be maintained on the other. The theories of ritual developed by the first half of the 20th century searched for the meaning and function of ritual beyond its domain. Ritual was considered as the fulfillment or expression of religious beliefs that had preceded it. It was considered to be somewhat secondary and derivative, and its explanation should be sought beyond ritual. At present ritual is considered to be a sui genesis phenomenon, which requires an autonomous theoretical explanation and its own methodological approach. The most specific elements of democratic political life are election campaigns which stand for ‘the whole complex of activities and actions of political parties and candidates who compete in the elections as they endeavor to win voters’. As I attempt to demonstrate the presence of ritual inside campaign I treat some events occurring in the framework of elections as separate and autonomous rituals and I emphasize the ritual (symbolic, expressive and communicative) nature or aspect of activities and actions undertaken (ritualization).